Report on the Observance of Standards and Codes : Corporate Governance Country Assessment, Republic of Indonesia - World Bank (Washington, DC, 2013)
In reforming its corporate governance, and in establishing a rule-based business culture, Indonesia faces many challenges. The key challenges are as follows. Enforcement of laws and regulations needs to be strengthened. Administrative sanctions for violation of securities or disclosure rules may not be adequate. Efforts should be expended to ensure that corporate officials in the position of trust are held accountable when they violate the law. Sanctions should go beyond fines, and the incentive system should be changed so that violators are truly discouraged, and good corporate behavior is promoted. This requires strengthening enforcement capacity of Bapepam for securities violations, and its independence as the securities regulator. The Company Law should explicitly refer to the fiduciary duties of directors and managers for violation of securities laws. Current efforts to amend the Company Law need to be expedited. Further efforts should also be expended to develop alternative (non-judiciary) mechanisms, such as shareholder activism, for encouraging compliance.